Komparasi E-Modul dan Media Pembelajaran Berbasis Android Terhadap Hasil Belajar Siswa di Tinjau dari Motivasi Belajar Siswa - Hendro Ganceh; Winda Rahmadita; Dinna Aulivia Mifthachul Jannah; Ferdy Julianto (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study was to determine the differences in student learning outcomes using e-modules and android-based learning media. And also to find out the differences in student learning outcomes in terms of student learning motivation. The research method used is an experiment with a factorial design. The population in this study consisted of 4 classes and the number of samples was 2 classes with 64 students. In practice, 1 class uses e-modules and the other class uses android-based learning media. Based on the results of the study, the class that uses the e module gets a higher average value than the android-based learning media class. This is because the e-module is easier to use and lighter when installed on a student's smartphone.